Spousal concordance in joint and separate households: Survey evidence from Nepal - Ambler, Kate; Doss, Cheryl R.; Kieran, Caitlin; Passarelli, Simone (International Food Policy Research Institute, 2020)
Using data from Nepal, we analyze patterns of concordance between spouses on survey questions regarding asset ownership and decision making separately for households in which a respondent couple lives with the husband’s parents and those in which they do not. We consider concordance regarding both the roles of women respondents and the roles of people other than the respondent couple. We find that discordance regarding women’s roles is both substantial and systematic; women are much more likely than men to report women’s participation in asset ownership and decision making, and this qualitative pattern is similar across household types. Regarding the role of others, the modal response in joint households is concordance that others own assets and make decisions. However, women are more likely than men to acknowledge this role of others. Next, we find that spousal concordance that women have a role, and wives reporting they have a role while their husbands say that they do not, are both correlated with some improved measures of well-being. In households with in-laws present, concordance that others are involved is correlated with worse outcomes for women. These results highlight that spousal concordance is not necessarily indicative of women's well-being, especially in joint households.